Effect of Self-Regulated Learning Strategy on students' achievement in Basic Science in Makurdi Local Government, Benue State, Nigeria - Christy Mbakohol Jirgba; Joy Iember Bur (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2019)
This study examined the effects of self-regulated learning instructional strategy on students' achievement in basic science among Upper Basic 2 in Makurdi Local Government Area of Benue State. The study employed non-equivalent group pre-test-post-test quasi experimental design. The population of the study was 638 upper basic school levels. The sample for this study was 128 students from six co-educational schools within Makurdi Local Government Area of Benue State. Two research questions and two hypotheses guided the study. The instrument used for data collection was Basic Science Achievement Test (BSAT) and was trial tested using Kuder-Richardson (K-R, 20) formula to determine the reliability coefficient of BSAT which was found to be 0.99. Descriptive statistics of means and standard deviation were used to answer all the research questions and inferential statistics of Analysis of Covariance (ANCOVA) was used to test all the hypotheses at 0.05 significant level. The results of the study showed that demonstration method enhanced students' achievement in basic science better than self-regulated strategy. There is no significant difference between the mean achievement score of students taught basic science using self-regulated learning strategy and those taught using demonstration method. There was no significant difference between the mean achievement scores of male and female students taught basic science using self-regulate learning strategy. Basic science Teachers should not only use demonstration method to teach but also allow the student to actively participate in the learning. This can foster confidence in the students and enhance better achievement in basic science.